2004
DOI: 10.1074/jbc.m308600200
|View full text |Cite
|
Sign up to set email alerts
|

Unique in Vivo Modifications of Coagulation Factor V Produce a Physically and Functionally Distinct Platelet-derived Cofactor

Abstract: Platelet-and plasma-derived factor Va (FVa) serve essential cofactor roles in prothrombinase-catalyzed thrombin generation. Platelet-derived FV/Va, purified from Triton X-100 platelet lysates was composed of a mixture of polypeptides ranging from ϳ40 to 330 kDa, mimicking those visualized by Western blotting of platelet lysates and releasates with anti-FV antibodies. The purified, platelet-derived protein expressed significant cofactor activity such that thrombin activation led to only a 2-3-fold increase in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
105
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(110 citation statements)
references
References 61 publications
(27 reference statements)
4
105
0
Order By: Relevance
“…Platelet factor V is more active in supporting clotting than is plasma factor V, and in particular, platelet factor V is activated by factor Xa at an accelerated rate relative to plasma factor V (9). Platelet factor V is structurally modified compared to the plasma protein, which may help explain its enhanced activity (8,10). We propose that an additional factor enhancing the procoagulant function of platelet factor V is the concomitant secretion of polyP upon platelet activation, and that polyP serves as a cofactor to enhance the rate of factor V activation by both thrombin and factor Xa.…”
Section: Resultsmentioning
confidence: 99%
“…Platelet factor V is more active in supporting clotting than is plasma factor V, and in particular, platelet factor V is activated by factor Xa at an accelerated rate relative to plasma factor V (9). Platelet factor V is structurally modified compared to the plasma protein, which may help explain its enhanced activity (8,10). We propose that an additional factor enhancing the procoagulant function of platelet factor V is the concomitant secretion of polyP upon platelet activation, and that polyP serves as a cofactor to enhance the rate of factor V activation by both thrombin and factor Xa.…”
Section: Resultsmentioning
confidence: 99%
“…3 This platelet-derived FV pool originates solely from megakaryocyte endocytosis of the plasma procofactor through a process that results in the formation of a partially proteolytically activated cofactor (FV/Va) 4 and phenotypically alters it to a more procoagulant phenotype. [4][5][6][7][8][9][10] The most common treatment of individuals with symptomatic FV deficiency is administration of fresh frozen plasma (FFP) to temporarily maintain plasma FV at minimally hemostatic levels (20% to 30%). 11 Its effect on platelet-derived FV/Va concentrations is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Given the success rate with steroids alone this is a reasonable first line treatment. In some cases, where patients have recurrence of the inhibitor, rituximab has been used as maintenance treatment with good results [14]. 60% of asymptomatic patients in this cohort had remission of the inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…20% of our factor V is stored in platelets and this FV seems to have different properties that allows it to escape FV inhibitors [12,13]. There is also evidence to suggest functionally distinct features of platelet and plasma FV [14,15]. One small study showed that patients with severe congenital FV with undetectable plasma FV had functional FV in their platelets [6].…”
Section: Discussionmentioning
confidence: 99%